Body Structure and Operation Features of Mongolian High Ranked Male Athletes - Shagdar, Bat-Erdene; Galsan-Yondon, Sukhbat; Sundui, Enebish; Amgalanbaatar, Gurbadam (Central Asian Journal of Medical Sciences, 2022)
Objectives: The purpose of this study is to determine the level of morphological and functional indicators depending on sports specializations among high-ranked Mongolian male athletes. Methods: Our study involved 218 athletes aged 18 - 34 in six sports and measured body composition by anthropometry and bioelectrical impedance. Physical performance was assessed by Harvard test, spirometry and physical fitness testing. Results: Sports specializations affect the indicators of physical development and body composition of athletes, which revealed significant differences between them. Martial arts athletes are stronger, more flexible, and more balanced than in team sports. As the ranks increase, body composition and performance get better. According to the Harvard test, 89.2 % (99) of team sports athletes and 98.2 % (55) of martial arts athletes received good and excellent marks. By the spirometry test, team sports groups have higher lung function results. Conclusion: Mongolian high-ranked male athletes have different body compositions in different sports types and it can create a profile of athletes within specific sports. Many years of training can improve the athlete’s performance. The cardiovascular function of athletes involved in martial arts quickly returns to normal after training. In team sports group, lung function is more adapted during a long period of training.